Solid-pseudopapillary neoplasm of the pancreas: A clinicopathological and immunohistochemical study of 33 cases from a single institution in Southern India - Shantveer G Uppin; Monalisa Hui; Venumadhav Thumma; Sundaram Challa; Megha S Uppin; Nagari Bheerappa; Regulagedda Adikesava Sastry; Tara Roshni Paul; Aruna K Prayaga (Wolters Kluwer Medknow Publications, 2015)
Background: The clinicopathological and immunohistochemical data of solid-pseudopapillary neoplasm (SPN) from India are limited. Our objectives were to evaluate various histopathological parameters and immunomarkers to elucidate the best possible immunomarker combination that can accurately diagnose these tumors. Materials and Methods: Clinicopathological features of 33 consecutive cases of SPN were retrospectively analyzed. Immunohistochemistry (IHC) was performed on a tissue microarray of 31 of these cases with antibodies to pan-cytokeratin (CK), vimentin, CD 10, E-cadherin, β-catenin, estrogen receptor (ER), progesterone receptor (PR), chromogranin. Results: Totally, 32 of 33 patients were females with a mean age of 26 years (range 12-62 years). Majority presented with abdominal pain (93.93%) and/or abdominal mass (48.48%). Location in pancreas included tail (14), head (7), body and tail (6), body (5) and neck (1). The mean diameter of the tumor was 8.6 cm (range 0.5-16 cm). Surgical exploration was done in all cases. On IHC, tumor cells were consistently positive for vimentin and negative for chromogranin (100%). CK was positive in 12 cases (38.7%), CD 10 showed perinuclear dot positivity in 14 (45.16%) cases and cytoplasmic positivity in 05 (16.12%) cases. All cases showed loss of membranous staining for both β-catenin and E-cadherin with nuclear positivity in 90.32% and 70.16% cases, respectively. PR was positive in 20 (64.51%) cases, while all of them were negative for ER. Conclusion: Solid-pseudopapillary neoplasm is a tumor commonly affecting young females. Loss of membrane expression of β-catenin and E-cadherin with nuclear positivity can be used confirm the diagnosis of SPN.